Shariah accountability practices of Islamic banks in Malaysia / Rosnia Masruki, Nur Sakinah Samsudin and Bablu Kumar Dhar - Masruki, Rosnia; Samsudin, Nur Sakinah; Dhar, Bablu Kumar (Faculty of Accountancy, 2019)
The study explores the concept of Shariah accountability, to promote transparency of Islamic Banks (IB) through Shariah disclosure by focusing on Shariah Committee report (SCR). This objective is achieved by using a quantitative method using a self-developed disclosure index, namely Shariah Disclosure Index (SDI). It was developed based on Bank Negara Malaysia (BNM) frameworks and guidelines, Accounting and Auditing Organisation for Islamic Financial Institution (AAOIFI) standards, Islamic Financial Supervisory Board (IFSB) regulations, and previous studies. Content analysis was conducted using the unweighted scoring method on seventy-five (75) annual reports from 2013 to 2017 for fifteen (15) IB in Malaysia to identify the level of SCR disclosure. The study findings show that the Shariah disclosure level of Malaysian IB only fulfills the minimum requirements by BNM, except for Bank Islam Malaysia Berhad (BIMB). Meanwhile, noted some IB disclosed the items under different headings in annual reports. Yet, there are few IB do not fulfil the minimum requirements of SCR disclosure. Thus, this study proposes a regulator to monitor SCR disclosure for IB, as specified by BNM and AAOIFI, since it is essential for conforming Shariah compliance.